Development and characterization of cellulose modified surface with allylthiourea as functional sites to remove basic red 5 from aqueous solution - Nazikussabah, Zaharudin; Farah Nurshahida, M. S.; Ahmad Salihin, Samsudin; Nurlin, Abu Samah (John Wiley & Sons, Inc., 2021)
In this work, the removal of Basic Red 5 (BR5) by using cellulose modified surface with allylthiourea as functional sites (CMS) was studied. CMS was prepared by acidification and then the activated cellulose was mixed with allylthiourea (AT) in acetonitrile to attached AT onto activated cellulose. There were five parameters have been studied including kinetic study, pH effect, saturation study, FTIR analysis and elemental analysis. As a result, the higher the concentration of the BR5 in the solution, the higher the percentage of removal. The most efficient pH to remove the BR5 by the CMS was at pH 7 with 80% of removal. pH effect gives significant impact in this work. Carbon, hydrogen and nitrogen content were found to be slightly increased after adsorption of BR5 due to BR5 was loaded with some additional of elements such as carbon, hydrogen and nitrogen. However, the sulfur content shows slightly decreased after adsorption of the BR5 due to the contribution of active functional sites of CMS depends on the thiol functional groups. However, the sulfur content shows slightly decreased after adsorption of the dye might be due to the contribution of active functional sites of CMS was depends on the thiol functional groups which has been bonded chemically with the BR5 during separation process in batch mode.